Knee joint contact stresses : the influence of deformity and muscle activity - Schmotzer, Hans (Division of Biomedical Engineering, 2017)
Studies have shown that the alignment of the knee in the coronal plane has a significant effect on the joint contact stress. However, gait analysis demonstrated that factors other than alignment contributed significantly to the outcome of corrective surgery. It was therefore hypothesized that muscle contraction can alter the stress distribution within the knee joint and that overloading can occur in the absence of a deformity. Six normal knees were harvested from different donors. The exact orientation of all muscle groups was recorded and their tendinous insertions carefully preserved. Custom built pressure transducers (6 per compartment, 0.5 mm thick, 10 mm diameter) were inserted through 2 small, posterior, capsular incisions and placed on the tibial surface and the menisci. The knees were mounted in a loading system which allowed free self-alignment of the joint under load. All muscles were replaced by wire cables instrumented with force transducer, tensioner and grip. Several alignment models (5, 10 degree varus, neutral, 5 degree valgus and 15 degree of flexion) as well as the effect of contraction of all major muscles crossing the knee joint were tested. An even pressure distribution was seen in neutral alignment. In a varus deformity the peak pressure shifted medially and laterally in valgus. Unloading of the opposite compartment was seen for deformities as small as 5 degrees. A flexion deformity produced a postero-lateral shift of the peak pressure area. Muscle contraction increased the pressure significantly in a region next to the muscle. Generally, unloading - though less significant - was seen in a region diagonally across the joint. These results suggest that muscular hyperactivity may considerable increase the contact stresses. However, muscle weakness or lack of muscular contraction may indirectly play a significant role in affecting the contact pressure distribution. If the muscle force is insufficient to counterbalance the external moment condylar lift-off occurs. This increases the angulation between femur and tibia thereby overloading the compartment where contact takes place; One can therefore conclude that abnormal gait patterns or neuromuscular control mechanisms may result in unphysiologically high contact stresses which may cause the development of unicompartmental osteoarthritis and subsequently, a deformity.